The transformation of the Springboks in the post-apartheid era: the end of a transition period (2013 - 2019)? - (:unkn) unknown (My University, 2021)
In 1995, the Rugby World Cup in South Africa was the field and embodiment of reconciliation between “Whites” and “non-Whites” sought by the first democratically elected “Black African” president, Nelson Mandela. The latter wanted, at the time, to make the national rugby team a symbol of unity in a country which had long been devastated by racial discrimination and the apartheid regime. The motto of the South African Rugby Federation (SARU) at this historic event was created to unite an entire country around “one team, one country”. This slogan emphasized the “non-racial” character of the Springbok team, which would no longer be selected on the basis of their racial affiliation but on the sole basis of merit. However, the fact that only one “coloured” player was in the Springbok team in 1995 was later criticized and the difficulty for the South African Rugby Federation (SARU) to reform/transform itself in order to be more representative of the different South African ethnic groups remains a burning issue which recently called for the implementation of affirmative action measures by the government.
Keywords: African Research